2019
DOI: 10.1002/aelm.201900576
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Stable Organic Permeable Base Transistors for Display Applications

Abstract: Unfortunately, high-resolution patterning techniques operating in the nanometer regime are costly and currently incompatible with the promise of low-cost flexible electronics. Hence, new device concepts need to be conceived which allow for an ultra-short channel length in conjunction with low fabrication costs. In this regard, vertical organic transistors with a channel length of ≈100 nm have generated significant interest in recent years, [4][5][6][7][8][9][10] as the vertical dimensions of an organic transis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…Later the focus shifted to p‐type OPBTs, where a similar level of performance had been reached . The real performance breakthrough though came with Fischer et al who reported in a series of papers on the continuous improvement of an n‐type OPBT, which ultimately led to the performance records mentioned previously. Furthermore, Fischer and co‐workers also developed a detailed theory on the device operation, which is used here for the discussion of the OPBT operation.…”
Section: Overview Over Device Principles and State‐of‐the‐artmentioning
confidence: 92%
See 2 more Smart Citations
“…Later the focus shifted to p‐type OPBTs, where a similar level of performance had been reached . The real performance breakthrough though came with Fischer et al who reported in a series of papers on the continuous improvement of an n‐type OPBT, which ultimately led to the performance records mentioned previously. Furthermore, Fischer and co‐workers also developed a detailed theory on the device operation, which is used here for the discussion of the OPBT operation.…”
Section: Overview Over Device Principles and State‐of‐the‐artmentioning
confidence: 92%
“…The huge potential for OPBTs to be used in high‐power and high‐frequency applications has very recently been underlined by Dollinger et al reporting for the first time on the electrical stability of OPBTs under high‐power stress conditions. In this publication, Dollinger judged on the device stability by means of the threshold voltage shift Δ V th which has been measured under continuous off‐state stress (electric field stress at 0.1 MV cm −1 ), but most importantly also under continuous on‐current stress at a high current density of 3 A cm −2 .…”
Section: Overview Over Device Principles and State‐of‐the‐artmentioning
confidence: 99%
See 1 more Smart Citation
“…One vertical organic transistor structure that stands out of all proposed approaches is the organic permeable base transistor (OPBT) which is the organic transistor with the highest transition frequency reported 29 . Furthermore, OPBTs show excellent stability comparable to the best lateral OTFTs 30 . However, complementary inverter circuits based on vertical organic transistors have not been reported so far which is mainly caused by the lack of proper p-or n-type transistors.…”
Section: Introductionmentioning
confidence: 94%
“…These devices offer very short channels compared to their planar counterparts because the thickness of a semiconductor layer can range from a few nanometers to several hundred nanometers. [ 11–16 ]…”
Section: Introductionmentioning
confidence: 99%